Pemberdayaan Masyarakat Melalui Edukasi Dan Pelatihan Pembuatan Jamu Herbal Lambung Berbasis Tanaman Herbal Sebagai Inovasi Program Kuliah Kerja Nyata (KKN) Tematik Unikal 2026 Dalam Meningkatkan Pengetahuan Masyarakat Di Desa Pekiringanageng - Sanimatul Habibah; Arina Manasikkana; Putri Maharani; M.Afrianto Andy Saputro; Dwi Setiani; Hevey Salsabila; Sindy Claudia; Alifka Citra Safitri; Khusnul Fadlillah; Putri Ragil Rihhadatul‘Aisy; Yusuf Ardhitya Purwanto (CV. SINAR HOWUHOWU, 2026)
Stomach disorders are one of the health problems often experienced by the community due to unhealthy eating habits, high stress levels, and minimal knowledge about prevention and self-treatment efforts. On the other hand, Pekiringanageng Village has the potential for herbal plants that can be used as an alternative to support stomach health, but its utilization is still not optimal due to the low level of community knowledge in processing herbal plants into safe and beneficial products. Based on these conditions, the 2026 UNIKAL Thematic Community Service Program (KKN) in Pekiringanageng Village held community empowerment activities through education and training in making herbal plant-based stomach herbal medicine as one of the community service innovations that was held on June 21, 2026. This activity aims to increase knowledge about the benefits of herbal plants and the correct method of making stomach herbal medicine. The implementation method used was in the form of socialization and direct practice regarding the benefits and how to process stomach herbal medicine. The results of the implementation showed an increase in the knowledge of the Pekiringanageng village community regarding the benefits of herbal plants, the composition of ingredients, the process of making stomach herbal medicine, and the importance of using herbal plants as an alternative to support family health.